2005
DOI: 10.1056/nejmoa042991
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Activated Factor VII for Acute Intracerebral Hemorrhage

Abstract: Treatment with rFVIIa within four hours after the onset of intracerebral hemorrhage limits the growth of the hematoma, reduces mortality, and improves functional outcomes at 90 days, despite a small increase in the frequency of thromboembolic adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
634
0
42

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 1,150 publications
(685 citation statements)
references
References 19 publications
9
634
0
42
Order By: Relevance
“…2,4 Significant hematoma growth, which was defined as hematoma growth >33% or 12.5 mL has been reported in approximately one third of ICH patients. 7,[9][10][11] Because early hematoma growth is associated with poor functional outcome, identification of potential predictors for hematoma growth is crucial for early diagnosis and management.…”
Section: Discussionmentioning
confidence: 99%
“…2,4 Significant hematoma growth, which was defined as hematoma growth >33% or 12.5 mL has been reported in approximately one third of ICH patients. 7,[9][10][11] Because early hematoma growth is associated with poor functional outcome, identification of potential predictors for hematoma growth is crucial for early diagnosis and management.…”
Section: Discussionmentioning
confidence: 99%
“…Improved ischemic stroke care is due to both the widespread use of specific therapies, such as thrombolysis, and to the management of ischemic stroke at stroke units. Only recently has a new therapeutic approach shown promising data in patients with ICH [24, 25] – the use of activated factor VII.…”
Section: Discussionmentioning
confidence: 99%
“…Although a phase 2 randomized trial showed that treatment with rFVIIa within 4 hours after ICH onset limited hematoma growth and improved clinical outcome relative to placebo, a subsequent phase 3 trial did not find clinical benefit. 108,109 Use of rFVIIa was associated with an increased frequency of thromboembolic events compared with placebo (7% versus 2%) in the phase 2 trial and significantly more arterial events in the phase 3 trial. It remains to be determined whether rFVIIa might benefit a particular subset of patients with ICH, but currently its benefits in ICH patients, whether or not they are taking an OAC, remain unproven.…”
Section: Antiplatelet Medication-related Ichmentioning
confidence: 99%